Feasibility and legitimacy of land use regulatory instruments in three agrarian reform settlements in northwest Mato Grosso, Brazil: the influence and role of integrated conservation and development - Davenport, Robert (2013)
Tesis (Mag.Sc.) -- CATIE, 2013